2015
DOI: 10.1039/c5tc00125k
|View full text |Cite
|
Sign up to set email alerts
|

Infrared invisibility stickers inspired by cephalopods

Abstract: The skin morphology of cephalopods endows them with remarkable camouflage capabilities. Herein, we report infrared invisibility stickers inspired by the structures and proteins found in cephalopod skin. These stickers enable arbitrary objects to acquire reconfigurable infrared camouflage patterning. Our work represents an initial step towards wearable biomimetic infrared stealth technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 29 publications
(76 reference statements)
1
81
0
Order By: Relevance
“…[16][17][18][19][20] Within this context, a number of literature reports have investigated the properties of unique structural proteins known as reectins, [7][8][9][10]14,[16][17][18][21][22][23][24] which are found in cephalopod skin cells (i.e. leucophores, iridophores, and chromatophores).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19][20] Within this context, a number of literature reports have investigated the properties of unique structural proteins known as reectins, [7][8][9][10]14,[16][17][18][21][22][23][24] which are found in cephalopod skin cells (i.e. leucophores, iridophores, and chromatophores).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Recently, these animals have drawn signicant attention as sources of novel materials for optical systems, 7-10 biomedical technologies, [11][12][13][14][15] and bioelectronic devices. [16][17][18][19][20] Within this context, a number of literature reports have investigated the properties of unique structural proteins known as reectins, [7][8][9][10]14,[16][17][18][21][22][23][24] which are found in cephalopod skin cells (i.e. leucophores, iridophores, and chromatophores).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Morse showed that reversible phosphorylation of reflectin inside the iridophores changes the size and spacing of between the alternating layers, modulating the reflectance in the process. 3 Long Phan, graduate research assistant in the Gorodetsky group, explains: 'When the cephalopod skin decides it needs to change colour, acetylcholine is released, which causes a cascade of chemical reactions that ultimately cause the release of protein kinases and…”
Section: Biomimetic Researchmentioning
confidence: 99%
“…Using various chemical, mechanical and electrical stimuli, he has found a way to fine-tune the optical properties of coatings based on reflectin to bounce back particular wavelengths of lightnotably those in the near infrared. In February 2015, Gorodetsky and his colleagues showed that physically stretching films of these proteins resulted in a tunable shift in reflectance 4 .…”
Section: When Appearance Is Deceptivementioning
confidence: 99%